Magnetic composite material for antibiotic degradation and preparation method thereof
Through Cu-MOF derived magnetic Co@Cu/C composite materials as catalysts, the problem of difficult to efficiently remove sulfamethoxazole in water environments in the prior art is solved, and the degradation effect with high efficiency and strong anti-interference ability is achieved, and it has low cost and good recovery.
Patent Information
- Application Number
- CN202411868123.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The prior art is difficult to efficiently remove sulfonamide antibiotics, especially sulfamethyloxazole, in the aqueous environment, and the catalyst has poor anti-interference performance, making it difficult to maintain efficient degradation performance under different environmental conditions.
The magnetic Co@Cu/C composite material was used as a catalyst to synthesize Co/Cu-MOF at room temperature and calcined and modified under N2 atmosphere to prepare a magnetic Co@Cu/C composite material for activation of peracetic acid degradation of sulfamethoxazole.
The efficient removal of sulfamethoxazole in water is achieved, with a removal rate of up to 96.8%, and it still maintains good degradation performance under different environmental conditions (such as different pH values and different ions). The material has low cost, simple preparation process and good recovery.
Smart Images

Figure CN119771351A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal organic framework material preparation and water treatment technology, and specifically relates to a novel Cu-MOF derived magnetic Co@Cu / C composite material for antibiotic degradation and a preparation method thereof. Background Art
[0002] Discharges of industrial and domestic wastewater as well as agricultural fertilizers and pharmaceuticals transfer increasing amounts of pollutants into aquatic environments, thus raising critical questions about the removal of pollutants from wastewater. Antibiotics are widely used drugs that are released into water in increasing amounts and are often detected in rivers, sewage, and soil. Antibiotics have become a widespread emerging pollutant and have been shown to induce the growth of resistant bacteria and resistance genes. Due to the potential threat of antibiotics to organisms in aquatic environments and human health, the safe and effective removal of these emerging pollutants is urgently needed.
[0003] Sulfonamide antibiotics will have a series of effects on microorganisms, aquatic animals and human health after entering the water environment. Studies have shown that sulfonamide antibiotics have different degrees of ecotoxicological effects on organisms at different trophic levels, such as bacteria, algae, crustaceans, rotifers and fish, among which the impact on algae is particularly significant. For humans, sulfonamide substances are neurotoxic and are directly related to neurological and psychiatric diseases such as intestinal transport dysfunction, sensory disorders, and neuropsychiatric complications. After sulfonamide antibiotics are ingested by the human body, on the one hand, they will be absorbed by the intestinal tissue and endocrine system of the human body, affecting the immune function, central and peripheral nervous system; on the other hand, they will indirectly affect the function of the nervous system through the intestinal microbiota. In addition, bacteria that are under the stress of sulfonamide antibiotics for a long time will produce resistance genes through gene mutations, and continue to spread through transformation, transduction and conjugation transfer, so that more bacteria will acquire resistance to sulfonamide antibiotics, weakening their role in disease prevention and treatment, and affecting human health. In recent years, the pollution of sulfamethoxazole (SMX) in wastewater has attracted widespread attention. As a common sulfonamide antibiotic, SMX has a long half-life and is difficult to biodegrade. It has a high persistence in the water environment and is difficult to completely remove using biological or conventional physical methods. Currently, there is an urgent need for efficient and energy-saving treatment methods to solve the problem of SMX-containing wastewater.
[0004] Advanced Oxidation Processes (AOPs) with peracetic acid has the advantages of fast speed and high removal efficiency, and is considered to be one of the effective technologies for removing antibiotics. Peracetic acid (PAA), as a highly efficient oxidant, has many advantages in treating organic pollutants. Peracetic acid has a high oxidation potential (E01.0-1.96V) and can effectively decompose organic pollutants in water. Secondly, PAA produces fewer by-products and has low toxicity during water treatment, which is conducive to reducing secondary pollution. In addition, peracetic acid has a high tolerance for water matrix and is suitable for wastewater treatment with different water quality conditions. During the degradation process, the reactive oxygen species (ROS) produced by PAA can attack multiple functional groups of organic pollutants, thereby achieving efficient degradation. The development of catalysts with high catalytic activity is one of the key factors to solve the above problems. Metal-organic frameworks (MOFs) are a new generation of crystalline porous materials with a pore structure formed by metal ions or clusters and organic ligands through coordination bonds. They have been a research hotspot in the field of coordination chemistry in the past 20 years. MOFs show significant advantages in the degradation of organic pollutants, mainly reflected in their unique high specific surface area, designable porous structure and excellent chemical stability. The specific surface area of MOFs is as high as 1000 square meters / gram, which provides abundant active sites for organic pollutants and effectively improves the degradation efficiency. Its porous structure allows selective adsorption and catalytic reactions, and the designability of the structure allows researchers to customize MOFs according to the characteristics of different pollutants to achieve the best degradation effect. In addition, the chemical stability of MOFs ensures that the catalytic performance can be maintained under harsh environmental conditions, making them have great application potential in the field of organic pollutant degradation. Among the many metal or metal oxide catalyst materials, the development of copper-based metal organic framework materials is of great benefit to the stimulation of peracetic acid to improve the catalytic activity of the material. Therefore, there is an urgent need to develop a copper-based metal organic framework material to remove sulfonamide antibiotics in water environments.
[0005] In the prior art, some achievements have been made in the preparation method of Cu-MOF derivative materials, such as the Chinese patent application number: 202310945093.4, published on December 15, 2023, which discloses a patent document entitled "A SCN-Cu-MOFs nanomaterial and its preparation method and application". The patent proposes to carry out thiocyanate composite modification of copper-based metal organic framework materials (Cu-MOF), synthesize SCN-Cu-MOFs nanomaterials by hydrothermal method, and apply SCN-Cu-MOFs nanomaterials to catalytic degradation of tetracycline. However, the material The anti-interference ability and acid-base resistance are unknown, the actual application effect is still unclear, and the synthesis cost of the material is high. The recycling and treatment of the material after use is challenging, and the actual application is difficult; Chinese patent application number: 202311548896, published on February 23, 2024, discloses a patent document entitled "A method for preparing a copper-based metal organic framework material for olefin-alkane separation". The patent is to fix a copper-based metal organic framework containing divalent copper in a stable olefin gas flow, and perform a reduction reaction to obtain a metal organic framework adsorbent containing a monovalent copper active component. However, the material may have the risk of desorption, and is easily affected by the environment and easily causes secondary pollution; Chinese patent number 202411329819, published on October 29, 2024, discloses a patent document entitled "An antibacterial gallium-copper bimetallic MOF nanomaterial and its preparation method and application". The present invention provides an antibacterial gallium-copper bimetallic organic framework (Ga / Cu-MOF) nanomaterial. By adjusting the ion doping ratio, adding 2-methylimidazole and polyvinyl pyrrolidone regulators, and adding trifluoroacetic acid to adjust the pH, gallium and copper were successfully integrated to prepare Ga / Cu-MOF nanomaterials, which were used to load antibiotics to eliminate intracellular bacteria and biofilms. They were used in mouse skin lesion infection models and rat osteomyelitis infection models. However, the material preparation method is complicated and is used to load antibiotics to eliminate intracellular bacteria and biofilms, while sulfamethoxazole is a broad-spectrum antibiotic, and the applications of the two are quite different.
[0006] In the research technology of activated peracetic acid, there are also related patents. For example, China Patent No.: 202410884472, published on October 11, 2024, discloses a patent entitled "Preparation of iron-nitrogen-doped magnetic wheat straw biochar and its application in degrading new pollutants". The invention proposes a method for preparing iron-nitrogen-doped magnetic wheat straw biochar, and applies it to activated peracetic acid to degrade diclofenac sodium. However, the recyclability and stability of the material are unknown, and the actual application effect is unknown; China Patent Application No.: 202410983891, published on November 22, 2024, discloses a patent document entitled "Method for degrading cefazolin sodium by activating peracetic acid using reduced hematite". The pH range for efficient removal of antibiotics by this material is relatively narrow, thereby limiting the removal of antibiotics in acidic and alkaline environments.
[0007] In the research technology of sulfamethoxazole removal, there are already some better methods. For example, the Chinese patent application number is: 202211256009, the application publication date is January 20, 2023, and the patent document disclosed is named "A preparation method and application of sulfamethoxazole biochar adsorbent". The invention uses palm fiber, urea and FeSO4·7H2O by a one-step pyrolysis method to synthesize a new type of FeN co-doped biochar for adsorbing sulfamethoxazole. However, compared with metal organic framework materials, biochar materials have weaker catalytic activity, long catalytic time and low selectivity, and are difficult to regenerate. Chinese patent application number: 202411249933, application publication date October 11, 2024, discloses a patent document entitled "Method for removing sulfamethoxazole in water by in-situ etched carbon felt modified with iron phosphide". The ruthenium iridium titanium electrode is used as the anode and the FeP@ECC electrode is used as the cathode to remove sulfamethoxazole from the target wastewater. Compared with this patent, this method has high energy loss and may produce harmful by-products. It has strict requirements on reaction conditions and is not easy to achieve industrial treatment. Summary of the invention
[0008] In view of the defects and shortcomings of the existing technology for removing antibiotics from water and the poor anti-interference performance of the catalyst, the purpose of the present invention is to provide a magnetic composite material for antibiotic degradation in order to solve the above problems.
[0009] To solve the above problems, the present invention adopts the following technical solutions.
[0010] The present invention provides a magnetic composite material for antibiotic degradation, wherein the magnetic composite material is Co@Cu / C, and the preparation method thereof specifically comprises the following steps:
[0011] (1) Preparation of Co / Cu-MOF: Copper acetate monohydrate and cobalt chloride hexahydrate were dissolved in anhydrous ethanol to obtain solution A; 2,5-dihydroxyterephthalic acid was dissolved in anhydrous ethanol to obtain solution B; solution B was then slowly dripped into solution A at room temperature; the mixture was stirred under a magnetic stirrer for 24 h and centrifuged to obtain a precipitate; the precipitate obtained after centrifugation was washed with anhydrous ethanol and then dried to obtain Co / Cu-MOF.
[0012] The molar ratio of the cupric acetate monohydrate to the cobalt chloride hexahydrate is 2.3 to 19:1.
[0013] (2) Preparation of magnetic Co5@Cu / C composite material: The obtained Co / Cu-MOF is ground and calcined in a tubular furnace. After cooling, the derived magnetic Co@Cu / C composite material can be obtained.
[0014] Furthermore, in step (1), the molar ratio of cupric acetate monohydrate to cobalt chloride hexahydrate is 4:1.
[0015] Furthermore, in step (1), the drying condition is: drying at 60° C. overnight.
[0016] Furthermore, in step (2), the calcination conditions are: heating to 600°C at a heating rate of 2°C / min under N2 atmosphere for 120 min, and cooling at room temperature.
[0017] The magnetic Co@Cu / C composite material obtained by the above preparation method can be used in removing antibiotics from water.
[0018] Furthermore, the antibiotic is sulfamethoxazole.
[0019] The specific principle of the present invention is speculated as follows:
[0020] The SMX molecules in the wastewater are first adsorbed onto the surface of the derived magnetic Co@Cu / C composite material through its porous structure. The Cu, Co species and surface functional groups in the magnetic Co@Cu / C composite material are the main active sites for PAA activation. 1 O2 and RO·, where 1 O2 plays a leading role in the degradation of SMX. These strong oxidizing free radicals destroy the structure of SMX through oxidation reactions, ultimately achieving degradation.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The magnetic Co@Cu / C composite material of the present invention can effectively remove SMX from water. Under the conditions of an initial SMX concentration of 10 mg / L, a pH value of 7.28 for the original SMX solution, a PAA dosage of 0.5 mM, and a material dosage of 100 mg / L, the removal rate of SMX degraded by PAA activated by the magnetic Co@Cu / C composite material is 96.8% after 30 minutes of reaction, and the reaction process can reach equilibrium within 5 minutes.
[0023] (2) The magnetic Co@Cu / C composite material of the present invention is highly efficient in degrading antibiotics, and the material has anti-interference performance when catalyzing the degradation of SMX. - 、SO4 2- , Cl - And when humic acid HA is present, it can still maintain good degradation performance, and the removal of SMX in water is less affected by the acidity and alkalinity of the environment.
[0024] (3) The preparation process of the present invention is simple. Co / Cu-MOF is synthesized by stirring at room temperature, and the magnetic Co@Cu / C composite material is synthesized by programmed temperature controlled calcination modification. The raw material cost is low, the removal efficiency is high, the application range is wide, and the material is magnetic and easy to recycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The magnetic Co obtained according to Example 3 of the present invention 20 @Scanning electron microscope image of the morphology of Cu / C composite material.
[0026] Figure 2 The magnetic Co obtained according to Example 3 of the present invention 20 @Performance comparison test chart of Cu / C composite material on activated PAA degradation of SMX.
[0027] Figure 3 The magnetic Co obtained according to Example 3 of the present invention 20 @Cu / C composite material shows the removal effect of activated PAA on SMX degradation at different pH values of the initial solution.
[0028] Figure 4 The magnetic Co obtained according to Example 3 of the present invention 20 @Recyclability test diagram of Cu / C composite material.
[0029] Figure 5 The magnetic Co obtained according to Example 3 of the present invention 20 @Cu / C composite material activates PAA to degrade SMX and resists Cl - Performance test chart.
[0030] Figure 6 The magnetic Co obtained according to Example 3 of the present invention20 @Cu / C composite material activates PAA to degrade SMX and resist NO3 - Performance test chart.
[0031] Figure 7 The magnetic Co obtained according to Example 3 of the present invention 20 @Cu / C composite material activates PAA to degrade SMX and resists SO4 2- Performance test chart.
[0032] Figure 8 The magnetic Co obtained according to Example 3 of the present invention 20 @Cu / C composite material activated PAA to degrade SMX anti-humic acid performance test diagram. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments, but is not intended to be a specific limitation of the present invention.
[0034] Example 1
[0035] This embodiment provides a method for preparing a magnetic Co@Cu / C composite material for activating PAA to degrade antibiotics (wherein the metal cobalt doping amount is 5%, that is, the molar ratio of Cu(OAc)2·H2O to CoCl2·6H2O is 95:5), and the material is named Co5@Cu / C. The method comprises the following steps:
[0036] Preparation of Co / Cu-MOF: 0.3793g Cu(OAc)2·H2O and 0.0238g CoCl2·6H2O were dissolved in 25ml anhydrous ethanol to form solution A, and 0.2g DHTP was dissolved in 10ml anhydrous ethanol to form solution B. Then solution B was slowly dripped into solution A at room temperature. The mixture was stirred under a magnetic stirrer for 24h and centrifuged to obtain a precipitate. The precipitate obtained after centrifugation was dehydrated in ethanol 4 times. Finally, it was dried at 60°C overnight to obtain Co / Cu-MOF.
[0037] Preparation of magnetic Co5@Cu / C composite material: The obtained Co / Cu-MOF was placed in a tubular furnace and calcined under a N2 atmosphere. The temperature was increased to 600°C at a heating rate of 2°C / min and calcined for 120 min. The temperature was cooled at room temperature and the product was collected to obtain a magnetic Co5@Cu / C composite material.
[0038] Example 2
[0039] This embodiment provides a method for preparing a magnetic Co@Cu / C composite material for activating PAA to degrade antibiotics (wherein the metal cobalt doping amount is 10%, that is, the molar ratio of Cu(OAc)2.H2O to CoCl2.6H2O is 90:10). The material is named Co 10 @Cu / C The method comprises the following steps:
[0040] Preparation of Co / Cu-MOF: 0.3594g Cu(OAc)2·H2O and 0.0476g CoCl2·6H2O were dissolved in 25ml of anhydrous ethanol to form solution A, and 0.2g DHTP was dissolved in 10ml of anhydrous ethanol to form solution B. Then solution B was slowly dripped into solution A at room temperature. The mixture was stirred under a magnetic stirrer for 24h and centrifuged to obtain a precipitate. The precipitate obtained after centrifugation was dehydrated in anhydrous ethanol 4 times. Finally, it was dried at 60°C overnight to obtain Co / Cu-MOF.
[0041] Magnetic Co 10 @Cu / C composite material preparation: The obtained Co / Cu-MOF was placed in a tube furnace and calcined in a N2 atmosphere. The temperature was raised to 600°C at a heating rate of 2°C / min and calcined for 120 min. The temperature was cooled at room temperature and the product was collected to obtain magnetic Co 10 @Cu / C composite material.
[0042] Example 3
[0043] This embodiment provides a method for preparing a magnetic Co@Cu / C composite material for activating PAA to degrade antibiotics (wherein the metal cobalt doping amount is 20%, that is, the molar ratio of Cu(OAc)2·H2O to CoCl2·6H2O is 80:20). The material is named Co 20 @Cu / C The method comprises the following steps:
[0044] Preparation of Co / Cu-MOF: 0.3194g Cu(OAc)2·H2O and 0.0952g CoCl2·6H2O were dissolved in 25ml anhydrous ethanol to form solution A, and 0.2g DHTP was dissolved in 10ml anhydrous ethanol to form solution B. Then solution B was slowly dripped into solution A at room temperature. The mixture was stirred under a magnetic stirrer for 24h and centrifuged to obtain a precipitate. The precipitate obtained after centrifugation was dehydrated in ethanol 4 times. Finally, it was dried at 60°C overnight to obtain Co / Cu-MOF.
[0045] Magnetic Co 20@Cu / C composite material preparation: The obtained Co / Cu-MOF was placed in a tube furnace and calcined in a N2 atmosphere. The temperature was raised to 600°C at a heating rate of 2°C / min and calcined for 120 min. The temperature was cooled at room temperature and the product was collected to obtain magnetic Co 20 @Cu / C composite material.
[0046] Figure 1 The magnetic Co prepared in this example 20 @Scanning electron microscope image of the morphology of Cu / C composite material.
[0047] Example 4
[0048] This embodiment provides a method for preparing a magnetic Co@Cu / C composite material for activating PAA to degrade antibiotics (wherein the metal cobalt doping amount is 30%, that is, the molar ratio of Cu(OAc)2·H2O to CoCl2·6H2O is 70:30). The material is named Co 30 @Cu / C The method comprises the following steps:
[0049] Preparation of Co / Cu-MOF: 0.2795g Cu(OAc)2·H2O and 0.1428g CoCl2·6H2O were dissolved in 25ml anhydrous ethanol to form solution A, and 0.2g DHTP was dissolved in 10ml anhydrous ethanol to form solution B. Then solution B was slowly dripped into solution A at room temperature. The mixture was stirred under a magnetic stirrer for 24h and centrifuged to obtain a precipitate. The precipitate obtained after centrifugation was dehydrated in ethanol 4 times. Finally, it was dried at 60°C overnight to obtain Co / Cu-MOF.
[0050] Magnetic Co 30 @Cu / C composite material preparation: The obtained Co / Cu-MOF was placed in a tube furnace and calcined in a N2 atmosphere. The temperature was raised to 600°C at a heating rate of 2°C / min and calcined for 120 min. The temperature was cooled at room temperature and the product was collected to obtain magnetic Co 30 @Cu / C composite material.
[0051] The catalysts prepared in Examples 1-4 were tested for degradation of SMX by activated peracetic acid, respectively, at an initial SMX concentration of 10 mg / L, an initial SMX pH of 7.28, a PAA dosage of 0.5 mM, a catalyst dosage of 100 mg / L, an oxidative degradation time of 8 min, a water temperature of 25 ° C, and an oscillation speed of 200 rpm / min. The test data show that the magnetic Co@Cu / C composite material obtained in Examples 1-4 of the present invention has a significant effect on the degradation of SMX by activated peracetic acid (as shown in Table 1).
[0052] Table 1 Experimental results of different examples of activated peracetic acid to remove SMX
[0053]
[0054] Example 5
[0055] This example is the magnetic Co prepared in Example 3 20 @Removal rate test of SMX catalytic degradation by PAA activated by Cu / C composite material.
[0056] The magnetic Co prepared in Example 3 20 @Cu / C composites are used to synergistically stimulate PAA to degrade SMX as follows:
[0057] Weigh 5 mg of magnetic Co 20 @Cu / C composite material was placed in a 100mL glass bottle, and 50mL SMX (initial concentration was 10mg / L) solution was added. The pH of the SMX stock solution was 7.28, and the PAA dosage was 0.5mmol / L. The degradation experiment was carried out in a constant temperature water bath oscillator at 200rpm / min. At regular intervals, 2mL of the reaction solution was taken, filtered with a 0.45μm filter membrane, and quenched with 100mM sodium thiosulfate. The experimental time was 8min, and the concentration change was measured by high performance liquid chromatography to calculate the degradation rate. Figure 2 As shown, when the material prepared in Example 3 is used to activate PAA to degrade SMX, the degradation rate can reach 96.8% in 8 minutes.
[0058] Example 6
[0059] This embodiment is the magnetic Co in embodiment 3 20 @Cu / C composite material removal rate test of SMX in different pH ranges. Figure 3 As shown, the pH value of the reaction system solution was adjusted to 3-11, and the magnetic Co 20 @Cu / C composite materials can still play a good catalytic degradation effect.
[0060] Example 7
[0061] This example is the magnetic Co prepared in Example 3 20 @Recyclability test of Cu / C composite materials.
[0062] In practical use, the catalyst must not only be efficient and convenient, but also be reusable and stable. 20 @The degradation effect of SMX during the four-time reuse of Cu / C composite material is as follows Figure 4As shown in the figure, the degradation rates of SMX after four reuses were 96.8%, 95%, 90% and 88.8% respectively. When the catalyst was reused four times, it still had a good removal effect on SMX.
[0063] Comparative Example
[0064] This comparative example is the magnetic Co prepared in Example 3 20 @Anti-interference test when Cu / C composite material activates PAA to degrade SMX.
[0065] In the degradation performance test of Example 5, 1-20 mmol / L of interfering ions Cl were added respectively. - 、NO 3- 、SO4 2- or 1-20mg / L humic acid, such as Figure 5-8 As shown, 20mmol / LCl was added to the system - 、NO 3- 、SO4 2 Or 20mg / L humic acid, the degradation rates of SMX were 85.6%, 91.8%, 90% and 82.2% respectively, proving that the material has strong anti-interference ability.
Claims
1. A magnetic composite material for antibiotic degradation, characterized in that: The magnetic composite material is Co@Cu / C, and its preparation includes the following steps: (1) Preparation of Co / Cu-MOF: Copper acetate monohydrate and cobalt chloride hexahydrate were dissolved in anhydrous ethanol to obtain solution A; 2,5-dihydroxyterephthalic acid was dissolved in anhydrous ethanol to obtain solution B; then solution B was slowly dripped into solution A at room temperature; the mixture was stirred under a magnetic stirrer for 24 hours, and a precipitate was obtained after centrifugation; The precipitate obtained after centrifugation was washed with anhydrous ethanol and then dried to obtain Co / Cu-MOF; The molar ratio of the copper acetate monohydrate to the cobalt chloride hexahydrate is 2.3 to 19:1; (2) Preparation of magnetic Co5@Cu / C composite material: The obtained Co / Cu-MOF is ground and calcined in a tubular furnace. After cooling, the derived magnetic Co@Cu / C composite material can be obtained.
2. A magnetic composite material for antibiotic degradation according to claim 1, characterized in that: In step (1), the molar ratio of cupric acetate monohydrate to cobalt chloride hexahydrate is 4:
1.
3. The magnetic composite material for antibiotic degradation according to claim 1, characterized in that: In step (1), the drying refers to: drying at 60°C overnight.
4. The magnetic composite material for antibiotic degradation according to claim 1, characterized in that: In step (2), the calcination refers to: heating the temperature to 600°C at a heating rate of 2°C / min under N2 atmosphere for 120 min, and cooling the temperature at room temperature.
5. Use of the magnetic composite material as described in any one of claims 1 to 4 in removing antibiotics from water.
6. The use of the magnetic composite material as claimed in claim 5 in removing antibiotics from water, characterized in that: The antibiotic is sulfamethoxazole.
Citation Information
Patent Citations
Preparation method and application of novel Cu-MOF derived magnetic Fe3O4atCu / C composite material for antibiotic degradation
CN116789977A
Preparation method and application of cobalt-iron alloy catalyst wrapped by magnetic carbon
CN117138786A
Magnetic cobalt-copper-based catalyst, preparation method thereof and application of magnetic cobalt-copper-based catalyst in wastewater treatment
CN117531511A
Magnetic monatomic cobalt catalyst and method for catalyzing peracetic acid to degrade antibiotics by using magnetic monatomic cobalt catalyst
CN117599794A
CoFe2O4-WTRs Composite Magnetic Catalyst, Preparation Method and Application Thereof
US20200238268A1